MENGEMBANGKAN KEMAMPUAN KREATIVITAS MEWARNAI PADA PESERTA DIDIK USIA DINI DENGAN KEGIATAN FINGER PAINTING - FACHRURRAZI, AHMAD; SETYANINGSIH, ANA (Buana Pendidikan, 2019)
This research was motivated by children using Finger Painting activities to introduce the concept of mixing colors children can develop creativity. This study was used to determine Finger Painting activities on the creativity abilities of the participants in group B of Al-Hikmah Kindergarten Surabaya. Finger Painting activities are suitable for improving children's creativity, because there are aspects of creativity that appear in Finger Painting activities that provide an opportunity for children to imagine in determining any image that their children will get a picture idea or color idea. This research was conducted in in group B TK Al-Hikmah Surabaya. The sample technique used in this study is Nonprobability sampling with a form of saturated sampling. The data collected by instruments of performance observation sheet. and analyzed with a one-group pre-test post-test design. Based on the results of data analysis which shows that the value of t-count=4.20 is greater than t-table 1.734 with a significance level of 0.05 and 2.552 at the 0.01 significance level with N=19 which means the null hypothesis (Ho) is rejected and the working hypothesis (Hl) is accepted. It can be concluded that Finger Painting activities can influence to the children’s coloring creativity.